Epic heroes on screen - Augoustakis, Antony; Raucci, Stacie (Screening antiquity., 2018)
Since 2000, numerous heroes of the ancient world have appeared on film and TV, from the mythical Hercules to leaders of the Greek and Roman worlds. This collection brings together a range of perspectives on twenty-first century cinematic representations of heroes from the ancient world.